2022
DOI: 10.3390/nano12132254
|View full text |Cite
|
Sign up to set email alerts
|

Paper Biosensor for the Detection of NT-proBNP Using Silver Nanodisks as Electrochemical Labels

Abstract: We report on the use of silver nanodisks (AgNDs), having a diameter of 50 ± 8 nm and a thickness of 8 ± 2 nm, as electrochemical labels for the detection of a model metalloimmunoassay for the heart failure biomarker NT-proBNP. The detection method is based on an electrochemically activated galvanic exchange (GE) followed by the detection of Ag using anodic stripping voltammetry (ASV). The AgNDs labels are superior to Ag nanocubes and Ag nanospheres in terms of the dynamic range for both the model and NT-proBNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…By enabling the analysis and interpretation of NT-ProBNP levels through user-friendly mobile applications, these advancements are making cardiovascular monitoring more accessible outside traditional clinical settings. Additionally, the application of artificial intelligence and machine learning algorithms in interpreting biosensor data is enhancing the predictive accuracy of NT-ProBNP measurements, offering potential for personalized treatment regimens and improved patient outcomes in cardiovascular care [ 17 , 54 , 55 ]. A comparative analysis of various nanomaterial-based biosensors for NT-ProBNP detection is given in Table 1 .…”
Section: Technological Advancements In Nanomaterial-based Biosensors ...mentioning
confidence: 99%
“…By enabling the analysis and interpretation of NT-ProBNP levels through user-friendly mobile applications, these advancements are making cardiovascular monitoring more accessible outside traditional clinical settings. Additionally, the application of artificial intelligence and machine learning algorithms in interpreting biosensor data is enhancing the predictive accuracy of NT-ProBNP measurements, offering potential for personalized treatment regimens and improved patient outcomes in cardiovascular care [ 17 , 54 , 55 ]. A comparative analysis of various nanomaterial-based biosensors for NT-ProBNP detection is given in Table 1 .…”
Section: Technological Advancements In Nanomaterial-based Biosensors ...mentioning
confidence: 99%
“…Then, the group developed several immunosensors, where a GE/ASV electrochemical method was utilized to detect different shapes of AgNP labels. 104,[115][116][117][118][119][120][121][122] It was demonstrated that the shape of the AgNP played a crucial role in determining the detection efficiency of metalloimmunoassay based on GE/ASV process. Specifically, it was shown that the LOD and analyte detection range could be tuned by simply altering the shape of the silver nanoparticle.…”
Section: Effect Of Agnp Shape and Size On The Ge Reactionmentioning
confidence: 99%
“…8). 119 AgNDs were employed because they have a large surface area and contain minimal interior Ag atoms that can be shielded by Au skin. This leads to higher GE efficiency and better assay performance.…”
Section: Effect Of Agnp Shape and Size On The Ge Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, a number of analytical methods in the literature have been reported for the analysis of NT-proBNP, including radioimmunoassay (RIA) [ 11 ], colorimetry [ 12 ], fluorescent bead-based immunoassay [ 13 ], chemiluminescent immunoassay [ 14 ], dynamic light scattering [ 15 , 16 ], surface-enhanced Raman scattering [ 17 ], amperometric immunosensors based on enzyme label [ 18 ], silver nanoparticle label method [ 19 ], silver nanodisk label method [ 20 ], photoelectrochemical immunosensor method [ 21 ], electrochemiluminescent (ECL) immunosensor method [ 22 ], field-effect transistor biosensor method [ 23 ], giant magnetoresistance assay [ 24 ], and fluorescence-based lateral flow immunoassay [ 25 ]. While very sensitive electrochemical biosensors for the detection of NT-proBNP have been reported [ 18 , 19 , 20 , 21 , 22 , 23 ], the requirement of a reference electrode in electrochemical biosensors may be a weak point, as liquid junction error often exists in practical situations [ 26 ]. Optical sensors do not require a so-called reference optrode, and also have the advantages of immunity to electromagnetic interference.…”
Section: Introductionmentioning
confidence: 99%